Guru Pendidikan Agama Kristen Yang Profesional Dalam Meningkatkan Kecerdasan Spiritual Peserta Didik - Dami, Friderich Jhonnoto; Tari, Ezra (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2024)
This paper is founded on the premise that Christian religious education is crucial in forming students' moral character and spiritual life, and that skilled Christian religious education teachers are critical in enhancing students' spiritual intelligence. The author also did secondary research by reading relevant literature. The findings of this article demonstrate how critical it is for effective Christian religious education teachers to enhance students' spiritual intelligence. They have the capacity to assist communities in developing a spiritual attitude consistent with Biblical teachings, a close relationship with God, and a thorough grasp of Christian religious principles. Comprehensive religious knowledge, good communication skills, an outstanding spiritual life, and the implementation of the principles of 2 Timothy 3:10 in teaching practice are some of the teacher competencies and attributes. This paper seeks to improve our knowledge of how professional Christian religious education teachers assist students in developing spiritual intelligence. Based on the principles in 2 Timothy 3:10, the research in this paper provides important guidance for Christian religious education instructors on how to assist students build their spiritual intelligence. This research can also serve as a foundation for improved Christian religious education in forming students' moral fiber and spiritual lives.